The Effectiveness Of An Educational Intervention On Nursing Staff And Nursing Technicians’ Practices Toward The Prevention Of Health Care–Associated Infections In Critical Care Unit (The Review of Diabetic Studies, 2025)
Background: HCAIs remain one of the biggest challenges facing critical care units in terms of increased mortality and high healthcare and morbidity cost. Nursing staff can play a vital role in infection prevention; however, there are still a number of knowledge gaps and inconsistencies in adhering to evidence-based practice.The aim of this study, therefore, will be to establish whether a structured educational intervention can affect the practices of nursing staff in relation to the prevention of HCAI within a critical care unit.Methods: A quasi-experimental pre-test/post-test design was used that included a sample of 110 nursing personnel (68 registered nurses and 42 nursing technicians) caring for patients in the medical-surgical intensive care unit. Data collection was through a validated knowledge assessment tool and observational checklist at baseline, immediately post-intervention, and at 3-month follow-up. HCAI rates were also monitored across the study period.Results: Significant improvements were seen in nursing knowledge scores: pre-intervention, 60.1 ± 9.4; post-intervention, 82.3 ± 7.1; p < 0.001. Knowledge gains were consistent across both professional roles. Observed compliance with infection prevention practices increased from 54.2% to 87.5% (p < 0.001). At 3-month follow-up, knowledge retention remained high: 82.1 ± 7.4, and practice compliance sustained at 83.4%. HCAI incidence decreased from 12.4 to 6.8 per 1,000 patient-days (p = 0.002).Conclusions: A structured educational intervention significantly improved nursing knowledge and compliance with HCAI prevention practices in critical care settings. These improvements in knowledge and practice were sustained at 3-month follow-up and were associated with infection reduction. Regular targeted education should be included in ongoing quality improvement activities within intensive care units.